Is banning significance testing the best way to improve Applied Social Science research? – Questions on Gorard (2016) - Spreckelsen, T; van der Horst, M (SAGE Publications, 2016)
Significance testing is widely used in social science research. It has long been criticised on statistical grounds and problems in the research practice. This paper is an applied researchers’ response to Gorard’s (2016) 'Damaging real lives through obstinacy: reemphasising why significance testing is wrong' in Sociological Research Online 21(1). He participates in this debate concluding from the issues raised that the use and teaching of significance testing should cease immediately. In that, he goes beyond a mere ban of significance testing, but claims that researchers still doing this are being unethical. We argue that his attack on applied scientists is unlikely to improve social science research and we believe he does not sufficiently prove his claims. In particular we are concerned that with a narrow focus on statistical significance, Gorard misses alternative, if not more important, explanations for the often-lamented problems in social science research. Instead, we argue that it is important to take into account the full research process, not just the step of data analysis, to get a better idea of the best evidence regarding a hypothesis.